2020
DOI: 10.3390/mi11060557
|View full text |Cite
|
Sign up to set email alerts
|

Jet Electrochemical Micromachining of Micro-Grooves with Conductive-Masked Porous Cathode

Abstract: Surface structures with micro-grooves have been reported to be an effective way for improving the performance of metallic components. Through-mask electrochemical micromachining (TMEMM) is a promising process for fabricating micro-grooves. Due to the isotropic nature of metal dissolution, the dissolution of a workpiece occurs both along the width and depth. Overcut is generated inevitably with increasing depth, which makes it difficult to enhance machining localization. In this paper, a method of electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…According to the basic principle of electrochemical machining, under the action of voltage, the electrolyte is sprayed on the workpiece from the inside of the tubular electrode, forming an electric field. Since the mask is insulated, the range of action of the electric field between the electrode and the workpiece is effectively limited [33][34][35]. Therefore, the size and shape of the inlet section can be improved, and the taper of the inlet section due to electrochemical corrosion can be reduced.…”
Section: Simulation Analysis Of Electric Field Distributionmentioning
confidence: 99%
“…According to the basic principle of electrochemical machining, under the action of voltage, the electrolyte is sprayed on the workpiece from the inside of the tubular electrode, forming an electric field. Since the mask is insulated, the range of action of the electric field between the electrode and the workpiece is effectively limited [33][34][35]. Therefore, the size and shape of the inlet section can be improved, and the taper of the inlet section due to electrochemical corrosion can be reduced.…”
Section: Simulation Analysis Of Electric Field Distributionmentioning
confidence: 99%
“…Subsequent electrochemical micromachining dissolves the exposed area to create the surface texture. With this method, several kinds of surface texture can be prepared, such as micro cavity arrays and micro groove arrays [16]. Wang et al [17] reported fabrication of a micro cavity array with a diameter of 40 µm diameter on a metallic cylindrical surface by using TMEMM.…”
Section: Introductionmentioning
confidence: 99%
“…The dual parallel jet is widely used in fluid energy transmission [ 1 ], atomic energy conversion [ 2 ], dynamics [ 3 ], chemical industry [ 4 ], aviation [ 5 ], and other fields. And as an important actuator of the dual parallel jet, the nozzle has a great influence on electrostatic distribution [ 6 ], three-dimensional (3D) bioprinting [ 7 ], electro-osmotic fluid flow [ 8 ], jetting performance [ 9 ], metal microcomponents picking [ 10 ], energy transport, chemical combustion and pollutant generation [ 11 ]. Thus, it is of great significance to verify the parallel jet characteristics and microfluidic state in the nozzle by means of numerical simulation and experiments.…”
Section: Introductionmentioning
confidence: 99%